Ergonomic intervention in manual material handing at the waterjet area in the aircraft manufacturing company - Muhammad Izrin Burhanuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study was to solve the ergonomics issue of manual handing of the sanbag at waterjet area for anaircarft manufacturing company. This study adopted some ergonomic assessment tool to assess the level of the issue.